2008
DOI: 10.1523/jneurosci.2540-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Cation-π Interaction in the Binding Site of the Glycine Receptor Is Mediated by a Phenylalanine Residue

Abstract: Cys-loop receptor binding sites characteristically contain many aromatic amino acids. In nicotinic ACh and 5-HT3 receptors, a Trp residue forms a cation-π interaction with the agonist, whereas in GABAA receptors, a Tyr performs this role. The glycine receptor binding site, however, contains predominantly Phe residues. Homology models suggest that two of these Phe side chains, Phe159 and Phe207, and possibly a third, Phe63, are positioned such that they could contribute to a cation-π interaction with the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 32 publications
6
80
0
1
Order By: Relevance
“…1B). Loop D contributes to the complementary (Ϫ) side of the GlyR-binding pocket (11,26). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Loop D contributes to the complementary (Ϫ) side of the GlyR-binding pocket (11,26). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because Arg-65 forms a crucial component of the glycine-binding site (5,49), the nonconservative p.R65W mutation most likely disrupts glycine binding when functionally expressed with wild type subunits. Our finding that it is not trafficked to the surface when expressed as a homomer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using unnatural amino-acid derivatives of aromatic phenylalanine side chains has demonstrated that skeletal sodium channels form a cation-pi interaction with lidocaine and QX-314 at aromatic residue Phe1579 (Phe1760 in Na V 1.5), but not Tyr1586 (Tyr1767 in Na V 1.5) 25 . This class of electrostatic interaction occurs between a cation and the negative potential formed by the quadrupole moment on the face of an aromatic side chain 26,27 and has been shown to be responsible for ligand-receptor interactions in a variety of ion channels [28][29][30] . However, it remains to be shown whether such a cation-pi interaction is conserved in the cardiac sodium channel isoform and, more importantly, whether it is a general trait of all class I anti-arrhythmic drugs.…”
mentioning
confidence: 99%